KONDISI SOSIAL PEDAGANG KAKI LIMA DI DESA BIALO KECAMATAN GANTARANG KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This journal aims to examine the social conditions of street vendors in Bialo Village, Gantarang District, Bulukumba Regency. This study aims to determine the social conditions of street vendors and the obstacles of street vendors in improving their social life. This research is qualitative research using communication and sociological approaches and data collection techniques used in the study, namely observation, interviews, documentation, and reference tracing. This research was conducted in Bialo Village, Gantarang District, Bulukumba Regency.